Association between radiotherapy and prognosis in patients with small cell carcinoma of the bladder undergoing bladder-sparing surgery - Liang, Fuchao; Zhou, Fei; Qian, Xiaoyuan; Qin, Linghui; Wang, Jiange; Ding, Chen; Kuniduzi, Yasen; Zhang, Xuejun; Fan, Lianming (Frontiers in Oncology, 2023)
Background: Small cell carcinoma of the bladder is rare and has a poor prognosis. This study aimed to investigate whether radiotherapy after bladder-sparing surgery could improve the survival benefits of patients.Methods: This population-based retrospective cohort study used data from the Surveillance, Epidemiology, and End Results cohort in the United States to investigate small cell carcinoma of the bladder. Univariate and multivariate Cox regression analyses were used to identify significant risk factors influencing the clinical prognosis. A propensity score matching (PSM) algorithm was used to reduce the interference of confounding factors in each study group. The matched groups underwent Kaplan-Meier survival analysis to assess the potential survival benefits.Results: Univariate regression analysis demonstrated that age (P<0.001), tumour stage (T stage) (P=0.005), node stage (N stage) (P<0.001), chemotherapy (P<0.001), bone metastasis (P<0.001), liver metastasis (P<0.001), lung metastasis (P=0.005), tumour size (P=0.005), and radiotherapy (P<0.001) were related factors affecting survival. Multivariate regression analysis revealed that age (P=0.001), T stage (P=0.054), N stage (P<0.001), radiotherapy (P=0.010), chemotherapy (P<0.001), bone metastasis (P=0.007), and liver metastasis (P<0.001) were independent factors affecting survival. Moreover, survival analysis was performed on the PSM-matched groups, leading to the following findings: (1) the radiotherapy group exhibited a superior survival prognosis compared with the non-radiotherapy group (P<0.001); (2) the survival prognosis of individuals who underwent This is a provisional file, not the final typeset article radiotherapy and chemotherapy was higher than that of those who underwent chemotherapy alone (P<0.001).The findings of this study suggest that radiotherapy improves survival benefits for patients with small cell carcinoma of the bladder who undergo bladder-sparing surgery. Furthermore, radiotherapy combined with chemotherapy demonstrates a greater survival benefit compared with chemotherapy alone. The results underscore the importance of considering radiotherapy as a valuable treatment option for such patients, highlighting its potential benefits in improving their overall prognosis.